IMPLEMENTASI PENDIDIKAN AGAMA DAN KE AGAMAAN PASCA KONFLIK DI MAN ADO - Sirajuddin Ismail (Balai Penelitian dan Pengembangan Agama Makassar, 2008)
This research aims to describe implementation of religion education.This was conducted at Manado, North Sulawesi. Data was collected bydepth interview and observation.This research indicates that implementation of religion education isrunning normally. Education problem in Manado is decreasing numberof teacher